Enhance production of fungal cellulase cocktail using cellulosic waste - Srivastava N.; Elgorban A.M.; Mishra P.K.; Marraiki N.; Alharbi A.M.; Ahmad I.; Gupta V.K. (My University, 2025)
This study reports improved production of crude fungal cellulase following solid-state fermentation (SSF). The lab isolate fungal strain shows enhanced cellulase production and has been identified as the Cladosporium cladosporioides NS2 using 18S ribosomal DNA sequencing pattern. An initial pH of 4.0 and temperature 30 °C is recorded to be optimum for maximum cellulase production. Among different types of carbon sources used, sugarcane bagasse offers the maximum production of FP (16.9 IU/gds), β-glucosidase (200 IU/gds) and EG (150 IU/gds) activity. In addition, among different types of nitrogen sources, peptone yields maximum production of EG (170 IU/gds), FP (17.5 IU/gds) and β-glucosidase (225 IU/gds). Moreover, among various types of metal ions, manganese ion (Mn++) gave the highest production of FP (20 IU/gds), β-glucosidase (240 IU/gds) and EG (210 IU/gds). © 2020